Influence of Maturity Stage and Postharvest Calcium Chloride Treatment on the Quality and Storage Life of Tomatoes (Lycopersicon esculentum, Mill) - Arthur, Eric (2014)
A Thesis Submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology as a partial fulfillment of the Requirement for the Award of Master of Science Degree in Food Science and Technology, March-2014